2013
DOI: 10.12932/ap0272.31.4.2013
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of ANA and anti-dsDNA in the diagnosis of systemic lupus erythematosus: A comparison using control sera obtained from healthy individuals and patients with multiple medical problems

Abstract: ANA and anti-dsDNA gave high sensitivity and high specificity in patients with SLE, even when using MMP patient's sera as controls. Physicians should take care in interpreting ANA and anti-dsDNA results in MMP patients who do not have signs or symptoms of SLE or connective tissue diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 30 publications
1
42
1
1
Order By: Relevance
“…It was clearly demonstrated that sensitivity and specificity of the test were 74 and 100%, respectively. Many of previous studies recorded high specificity of ELISA anti-dsDNA antibodies in SLE patients (Wichainun et al, 2013). Three sophisticated techniques were previously evaluated by multiple studies for the detection of anti-ds DNA antibodies in SLE patients; radioimmunoassay, immunofluorescent and ELISA techniques.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was clearly demonstrated that sensitivity and specificity of the test were 74 and 100%, respectively. Many of previous studies recorded high specificity of ELISA anti-dsDNA antibodies in SLE patients (Wichainun et al, 2013). Three sophisticated techniques were previously evaluated by multiple studies for the detection of anti-ds DNA antibodies in SLE patients; radioimmunoassay, immunofluorescent and ELISA techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Deposition of anti-dsDNA antibodies in certain renal structures has been linked to disease severity (Yung and Chan, 2008). High sensitivity and specificity of anti-dsDNA antibodies were concluded by various studies concerning with accurate and early detection of renal involvement in lupus patients (Wichainun et al, 2013). However, a negative anti-dsDNA findings may be observed in many patients suspected with LN.…”
Section: Introductionmentioning
confidence: 99%
“…3 Other studies calculated the specificity and sensitivity of ANA testing in diagnosing SLE as 92% and 98%, respectively. 4 Substituting these values into the calculations in the eTable in the Supplement gave a positive predictive value of 5.47% and negative predictive value of 99.99% (calculations not shown). Even with this improved sensitivity and specificity, for every true-positive ANA test result, there were 19 false-positive test results.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-double stain antibodies (anti-dsDNA) is rarely used for SLE screening, because the sensitivity is only 70%, however anti-dsDNA has high specificity -99 % .On the first admission the patient had negative anti-dsDNA test. [11][12][13] The patient had low C3 level, which is one of the diagnostic criteria of SLE. During pregnancy compliment C3 and C4 level, increased due to oestrogen induced synthesis in the liver.…”
Section: Discussionmentioning
confidence: 99%